2018
DOI: 10.1038/s41418-018-0067-x
|View full text |Cite
|
Sign up to set email alerts
|

TMCO1 is essential for ovarian follicle development by regulating ER Ca2+ store of granulosa cells

Abstract: TMCO1 (transmembrane and coiled-coil domains 1) is an endoplasmic reticulum (ER) transmembrane protein that actively prevents Ca2+ stores from overfilling. To characterize its physiological function(s), we generated Tmco1−/− knockout (KO) mice. In addition to the main clinical features of human cerebrofaciothoracic (CFT) dysplasia spectrum, Tmco1−/− females manifest gradual loss of ovarian follicles, impaired ovarian follicle development, and subfertility with a phenotype analogous to the premature ovarian fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…The results demonstrated that TMCO1 had a relationship with A549 cells viability and migration. TMCO1, as a regulator of cellular calcium ions, was shown to affect numerous growth factors, which was in accordance with previous reports demonstrating that calcium ions participate in the regulation of numerous biological functions through complex networks (31,32). In the present study, immunostaining was performed to observe changes in the expression levels of associated proteins, which suggested that TMCO1 participated in A549 cell biological processes.…”
Section: Discussionsupporting
confidence: 91%
“…The results demonstrated that TMCO1 had a relationship with A549 cells viability and migration. TMCO1, as a regulator of cellular calcium ions, was shown to affect numerous growth factors, which was in accordance with previous reports demonstrating that calcium ions participate in the regulation of numerous biological functions through complex networks (31,32). In the present study, immunostaining was performed to observe changes in the expression levels of associated proteins, which suggested that TMCO1 participated in A549 cell biological processes.…”
Section: Discussionsupporting
confidence: 91%
“…The results suggested that ER stress signaling pathway was involved in autoimmune‐induced POF mice. Studies have shown that the normal physiological function of GCs is dependent on the homeostatic maintenance of ER Ca 2+ store (Sun et al, ). Therefore, in the present study, the GCs apoptosis of POF mice may be triggered by the ER stress response.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, pathogenesis of many autoimmune diseases is related to cell apoptosis caused by unfolded/misfolded proteins accumulation, including multiple sclerosis, rheumatoid arthritis, and inflammatory bowel disease (Hetz et al, 2013). Studies have confirmed that maintaining ER Ca 2+ homeostasis of GCs is important for ovarian follicle development (Sun et al, 2018). In addition, previous studies have shown that transplantation of hPMSCs improved the ovarian function of POF mice and reduced the expression of caspase-3 activation (Yin et al, 2018a).…”
Section: Introductionmentioning
confidence: 86%
“…The physiological function of TMCO1 is not fully elucidated, whereas it has been reported that it plays a key role in the maintenance of calcium ion homeostasis within the ER [248,249]. Furthermore, it has been suggested that TMCO1 may constitute an important protein in tumor suppression as well as play a crucial role in cell cycle regulation within the ocular tissues [250,251].…”
Section: Tmco1mentioning
confidence: 99%